Targeting Autophagy with Natural Compounds in Cancer: A Renewed Perspective from Molecular Mechanisms to Targeted Therapy - Xie, Qiang; Chen, Yi; Tan, Huidan; Liu, Bo; Zheng, Ling-Li; Mu, Yandong (Frontiers in Pharmacology, 2021)
Natural products are well-characterized to have pharmacological or biological activities that can be of therapeutic benefits for cancer therapy, which also provide an important source of inspiration for discovery of potential novel small-molecule drugs. In the past three decades, accumulating evidence has revealed that natural products can modulate a series of key autophagic signaling pathways in different types of human cancers. Autophagy, an evolutionarily conserved, multi-step lysosomal degradation process in which a cell destroys long-lived proteins and damaged organelles, has been widely reported to play a crucial role in several pathological processes, most notably in cancer. In this chapter, we focus on highlighting several representative natural active compounds, mainly including curcumin, resveratrol, paclitaxel, Bufalin, and Ursolic acid that may ultimately trigger cancer cell death for regulation of some key autophagy signaling pathways, involved in RAS-RAF-MEK-ERK, PI3K-AKT-mTOR, AMPK, ULK1, Beclin-1, Atg5 and p53. Taken together, these inspiring findings would shed new light on exploiting more and more natural compounds as candidate small-molecule drugs, by targeting the crucial pathways of autophagy for the future cancer therapy.